RANCANGAN FITUR SINGLE SIGN ON PADA PADA PERPUSTAKAAN XYZ - Armanda, Akbar Syahansyah; Shaleha, Imroatun; Fatwanto, Agung (Jurnal Informasi, Perpustakaan, dan Kearsipan (JIPKA), 2023)
The design of adding a single sign on feature to one-door login authentication is a system design that allows library users to do the authentication process once to access various library applications such as OPAC, circulation, and visits. This design aims to improve user convenience, efficiency, security, integration, and identity management in the context of application use at XYZ Library. In the design of adding single sign on feature to this one-stop login authentication, library users will start the login process by entering their authentication credentials into the authentication system. The authentication system will verify the credentials and provide a secure authentication token to the user. This token will be used to access library applications linked to the authentication system without the need to log in repeatedly. The main advantage of the design of adding single sign on feature to this one-stop login authentication is the convenience for users as they only need to authenticate once to access various library applications. This increases user efficiency and productivity, reduces the risk of leakage or misuse of user credentials, eases integration with existing library applications, and enables centralized identity management. In conclusion, the design of adding single sign on feature to the one-stop login authentication at XYZ Library provides significant benefits in terms of user convenience, efficiency, security, integration, and identity management. It enhances the library's user experience and facilitates access to available services and resources.Keywords: Authentication, Design, features, Single sign on